PELATIHAN TEKNOLOGI GENTENG CETAK TANPA SEMEN DAN PEMBAKARAN DARI TAILING MANGAN PADA UMK TAMBANG DI KEC. CIBALONG, KAB. TASIKMALAYA - Prof. Dr. Eng. Aripin, IPU.; Sutisna; Faridah, Linda; Purwanto, Anto (Sahira Publishing, 2025)
Kec. Cibalong, Kab. Tasikmalaya is 32 km from Siliwangi University and has manganese ore deposits. Kec. Cibalong has smallholder manganese ore mining with the management carried out by local. Two micro and small scale mining companies (UMK), namely the Bara Abadi and Mangan Jaya Companies as partners for community service activities and are local companies that accommodate and facilitate the marketing of people's manganese ore mining products. Both companies have an average of ten workers as miners. During the manganese ore exploration process, it generates residual waste in the form of manganese ore tailings from leaching. Estimates based on information made by the two partners indicate that for every tonne of manganese ore produced, two tonnes of manganese ore tailings are removed. Based on current production levels, it can be estimated that approximately 1,200 tonnes of manganese ore mine tailings are produced annually in Setiawaras Village. These manganese ore tailings are abandoned on roadsides, reservoirs, vacant lots and mining areas. The problems faced by partners are (1) the accumulation of manganese ore mine tailings disturbs and narrows the land for manganese ore mining activities, (2) manganese ore mining tailings causes soil and groundwater pollution, (3) limited knowledge and skills of partners in processing manganese ore tailings products into quality printed roof tiles, (4) limited equipment for the production process of molded bricks from manganese ore mine tailings. The objectives of this program are (1) to increase the added value of manganese ore mining tailings through downstream processing of tailings into molded roof tiles for building materials, (2) to increase the knowledge, insight and skills of the partners group in the manufacture of molded roof tiles without burning from manganese ore mine tailings, and (3) equip production equipment to convert manganese ore mine tailings into molded tile products. The number of participants was 5 members of the Bara Abadi and Mangan Jaya companies in Setiawaras Village. The training was held from 24 to 25 September 2022. This activity is carried out using training, practice, and mentoring methods. The training method is to provide materials on the procedures for making printed roof tiles from a mixture of manganese tailings and plastic waste adhesive. The practical method is carried out by practicing the preparation of fine manganese tailings, adhesive from plastic waste, heating a mixture of manganese tailings and plastic waste using a drum, molding dough with tile molds. The results of the training showed that the participants' interest in this activity was very good, especially for the aspects of tile printing, practicality, and community empowerment. From the aspect of operating activities, it indicated that participants could use and operate the tile printer independently without assistance.